STUDI KASUS KETERLAMBATAN PROYEK KONSTRUKSI DI PROVINSI JAWA TIMUR BERDASARKAN KONTRAK KERJA - FREDY KURNIAWAN; Diah Ayu Restuti Wulandari; Lilian Arlista Ayu (Program Studi Teknik Sipil Universitas Narotama, 2018)
The development of increasing infrastructure development gave birth to the rapid development of service companies engaged in construction. Delay is one of the obstacles to development because the completion time does not match the one specified in the employment contract document. The delay in the construction project means the increase in the timing of the completion of the planned project and is contained in the contract documents agreed by both parties, namely the first and second parties. This study is to look for factors that affect the delays of construction projects, identify the role of legislation, and identify contracts. This research method is qualitative that is by observation and interview with resource person from Dinas Pekerjaan Umum Dan Tata Ruang that is PPK and staff. Also speakers from private contractors are supervisors, structural estimators, and some staff. On the scope of Government projects, the three dominant factors that affect the construction project's delays are weather, labor, and design. On the scope of Private projects, the three dominant factors that affect construction project delays are weather, material, and finance. The laws governing the delay are Law No.2 / 2017 article 54 paragraph (1) and (2), Perpres No.54 / 2010 Jo Perpres No.35 / 2011 Jo Perpres No.70 / 2012 and LKPP No.14 / 2012. The clause on the delay in the government work contract is in the SSUK, namely the critical contract, the term SSKK, and the bank's guarantee. Clauses on Private contracts namely the breach of wanprestasi and sanctions, and bank guarantees.